1993
DOI: 10.1590/s0004-282x1993000200007
|View full text |Cite
|
Sign up to set email alerts
|

Valor do esfregaço no diagnóstico per-operatório dos tumores provenientes de neurocirurgias

Abstract: The smear technique has been used for rapid diagnosis of tumors removed in neurosurgeries in many neuropathological centers. In order to assess the diagnostic accuracy of this technique, we examined 137 smears and made a cytohistological correlation. Our cases include 12 astrocytomas, 4 anaplastic astrocytomas, 26 glioblastomas, 7 oligodendrogliomas, 5 medulloblastomas, 8 schwannomas, 17 meningiomas, 13 pituitary adenomas, 20 metastatic tumors and 18 assorted tumors and non neoplastic lesions. The correct diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
0
0
3
Order By: Relevance
“…The diagnostic accuracy of crush smears in this study was 91.25%, which was equivalent to other studies. [ 1 5 10 14 15 16 17 18 19 20 21 22 ] The diagnostic accuracy of frozen section was 95%, which was comparable to other studies. [ 5 14 16 ] It was found that frozen section technique was superior to crush smear in all cases, especially in lesions that were difficult to smear during the process of intraoperative diagnosis.…”
Section: Discussionsupporting
confidence: 75%
“…The diagnostic accuracy of crush smears in this study was 91.25%, which was equivalent to other studies. [ 1 5 10 14 15 16 17 18 19 20 21 22 ] The diagnostic accuracy of frozen section was 95%, which was comparable to other studies. [ 5 14 16 ] It was found that frozen section technique was superior to crush smear in all cases, especially in lesions that were difficult to smear during the process of intraoperative diagnosis.…”
Section: Discussionsupporting
confidence: 75%
“…Depois desta etapa, as lâminas eram coradas com azul de toluidina a 1% durante 1 minuto, depois lavadas em água corrente, passando rapidamente em álcool a 70%, álcool absoluto (duas vezes), xilol (duas vezes) e finalmente montadas com bálsamo e lamínula, conforme descrito previamente por Chimelli e Campos (1993) (7) .…”
Section: Materiais E Métodosunclassified
“…Além disso, a consistência amolecida do tecido do sistema nervoso central (SNC) torna fácil a realização de esfregaços (33) . O exame citológico também permite a análise de todo o material selecionado, diferentemente da congelação, em que apenas um pequeno segmento do material selecionado é examinado, pois em geral apenas um ou dois cortes consecutivos são realizados (7) , o que pode resultar em problemas no diagnóstico per-operatório, já que as neoplasias do SNC podem apresentar aspectos variegados (20) , dependendo da região analisada. O esfregaço fornece ainda maior preservação de detalhes nucleares e citoplasmáticos, que são perdidos durante a congelação, e esses detalhes são fundamentais para a exclusão de processos não-neoplásicos do SNC ou, no caso das neoplasias, para a determinação do tipo celular de origem (8,11) , cujas características no esfregaço já foram amplamente descritas (2,4,5,10,13,21,25,29,34,36) .…”
Section: Introductionunclassified
See 1 more Smart Citation